STRATEGIES FOR LAUNCHING NEW FACE TONER PRODUCTS: : INSIGHTS DERIVED FROM INSTAGRAM BEAUTY INFLUENCER REVIEWS - Suryaneta, Suryaneta; Sholeha, Aida Febina; Noviantoro, Tri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
The rapid and dynamic evolution of the cosmetics industry in Indonesia necessitates an equally dynamic approach to innovation and technology integration. The introduction of novel cosmetic products assumes paramount importance for businesses striving to not only thrive but excel within this fiercely competitive market. A compelling strategy for the successful launch of such products involves a comprehensive exploration of digital marketing avenues, with an emphasis on exploiting the vast landscape of social media platforms. In the context of introducing new products, particularly face toners, meticulous market research on widely embraced social media platforms like Instagram becomes an imperative. This research is dedicated to the meticulous scrutiny of recently unveiled face toner products in the year 2023, aiming to discern their prominence in user-generated comments within the domains of beauty influencer reviews. The focus of this analysis revolves around three distinctive products as Azarine, Aubree, and Elsheskin. The meticulous qualitative analysis of the amassed comment data has uncovered that the prominence of these products is not solely attributed to their efficacy; rather, it is significantly influenced by the allure of their packaging design and vibrant color schemes. This research serves as an invaluable resource for aspiring entrepreneurs and established cosmetic companies embarking on the endeavor to introduce fresh face toner products. The findings underscore the profound impact of product quality, aesthetics, and strategic marketing efforts in establishing a robust foothold in the fiercely competitive cosmetics market. Furthermore, this study unveils the strategies essential for the efficacious introduction and promotion of novel products in this dynamic industry.